Spatiotemporal Interactive Learning for Cloud Removal Based on Multi-Temporal SAR–Optical Images - Chenrui Xu; Zhenfei Wang; Liang Chen; Xiangchao Meng (Remote Sensing)
Optical remote sensing images suffer from information loss due to cloud interference, while Synthetic Aperture Radar (SAR), capable of all-weather and day–night imaging capabilities, provides crucial auxiliary data for cloud removal and reconstruction. However, existing cloud removal methods face the following key challenges: insufficient utilization of spatiotemporal information in multi-temporal data, and fusion challenges arising from fundamentally different imaging mechanisms between optical and SAR images. To address these challenges, a spatiotemporal feature interaction-based cloud removal method is proposed to effectively fuse SAR and optical images. Built upon a conditional generative adversarial network framework, the method incorporates three key modules: a multi-temporal spatiotemporal feature joint extraction module, a spatiotemporal information interaction module, and a spatiotemporal discriminator module. These components jointly establish a many-to-many spatiotemporal interactive learning network, which separately extracts and fuses spatiotemporal features from multi-temporal SAR–optical image pairs to generate temporally consistent, cloud-free image sequences. Experiments on both simulated and real datasets demonstrate the superior performance of the proposed method.